'Warren Buffet is my cousin': shaping public understanding of big data biotechnology, direct-to-consumer genomics, and 23andMe on Twitter. Issue 3 (4th March 2018) - Chow-White, Peter; Struve, Stephan; Lusoli, Alberto; Lesage, Frederik; Saraf, Nilesh; Oldring, Amanda
ABSTRACT: Scholars, educators, regulators, pundits, and other observers are advocating for regulation and oversight of direct-to-consumer (DTC) genomic testing. As a result, the technology has been subject of highly visible public and regulatory controversy. In this article, we explore the nature and the shape of the sentiment of public discourse about the DTC company, 23andMe. We conduct a quantitative content analysis and qualitative framing analysis on Tweets. We find that the discourse surrounding DTC genomics and 23andMe is largely positive. We also identify a number of frames users deploy to debate, discuss, and share their experiences with DTC genomics and 23andMe. We argue that these frames create meaning around this emerging technology for its users.